A Comparative Study to Evaluate the Effect of Blood Flow Restriction Therapy and Retro Walking on Pain, Strength of Muscles and WOMAC Score in Patients of Osteoarthritis of Knee - Indrani Gurjalwar; Deepali Patil; Kiran Kumar; Pratik Phansopkar (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background - Osteoarthritis of knee being of the major causes for disability in older population. Due tosedentary lifestyle this disease is becoming common in younger population as well. As prevalence of thedisease is increasing it is a need of the hour to come up with a highly reliable exercise protocol which will bebeneficial for the patients. This research aims to establish a beneficial and reliable exercise protocol whichcan be well tolerated by the patients suffering from osteoarthritis of knee.Methods – 150 subjects will be selected. Randomly they will be assigned to two groups that is Group A andGroup B using chit method. Group A will receive Blood Flow Restriction Training and Group B will receiveretro walking training. Training will continue for 15 days. After 15 days patient will be reassessed for pain,strength and WOMAC score.Result – Studies have proved that Blood Flow Restriction Therapy and retro walking both the interventionare beneficial in patients of osteoarthritis to reduce pain, improve strength and WOMAC score. This studywill provide us an intervention which is beneficial in treating osteoarthritis and is well tolerated by thepatients. We may get a result where blood flow restriction would have a better impact on few outcomemeasures while retro walking may fetch better impact on other outcome measures. We may also concludethat combination of both the interventions is a better option for the treatment of osteoarthritis patients.